1967
DOI: 10.1071/sr9670047
|View full text |Cite
|
Sign up to set email alerts
|

A classification of soil aggregates based on their coherence in water

Abstract: Soil aggregates have been divided into seven classes by observing the coherence of the clay fraction after reacting aggregates with water. The reactions used were: immersion of dry aggregates in water, immersion of wet remoulded aggregates in water, and suspension of aggregates in water. One further class was distinguished by the presence of carbonate. Illite and montmorillonite clays were modified so as to exhibit the physical properties of some of the aggregate classes. The results with the clays were then u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
5

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(118 citation statements)
references
References 0 publications
2
106
0
5
Order By: Relevance
“…Thus, it was surprising to note that H8 exhibited a very high dispersibility under the field conditions in spite of the small amount of charges. Regarding the dispersion behavior of illite, however, Emerson (1967) pointed out that a relatively small specific surface area of illite allowed water molecules to penetrate around the particles in the suspension, and as a result the dispersibility of illite was sometimes higher than that of montmorillonite.…”
Section: Factors Affecting Dispersion and Flocculation Behaviormentioning
confidence: 99%
“…Thus, it was surprising to note that H8 exhibited a very high dispersibility under the field conditions in spite of the small amount of charges. Regarding the dispersion behavior of illite, however, Emerson (1967) pointed out that a relatively small specific surface area of illite allowed water molecules to penetrate around the particles in the suspension, and as a result the dispersibility of illite was sometimes higher than that of montmorillonite.…”
Section: Factors Affecting Dispersion and Flocculation Behaviormentioning
confidence: 99%
“…An assessment of the literature has found that most researchers appear to misquote Emerson's (Emerson 1964;Emerson 1967) work and use his findings incorrectly. There have been many cases in which the method has been misinterpreted with regard to variables such as moisture content and dispersing medium (Heinzen & Arulanandan 1977;Bell & Maud 1994;Walker 1997;Bell & Walker 2000).…”
Section: Crumb Testmentioning
confidence: 99%
“…The methodology proposed by Emerson (1967) and Cerda (1998) was applied with no adaptations. Ten aggregates of 10 mm were put in 200 mL of water to evaluate its dispersion after 12; 24 and 36 hours, considering the scale: 0: no dispersion and aggregates completely stable; 1: dispersion of some particles, milkiness close to the aggregates; 2: Aggregates partly dispersed or divided into different smaller aggregates; 3: Considerable dispersion with most of the aggregates have been dispersed and milkiness very intense; 4: Total dispersion.…”
Section: Aggregate Dispersionmentioning
confidence: 99%